The seed tracker App - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
The seed tracker is an easy-to-operate tool covering all stages of the seed value chain. It has assisted farmers in locating and purchasing high-quality, disease resistant seed varieties that may be available. This tool has also helped to solve the problem of expensive seed regulation for smallholder seed producers.